Crude Polysaccharides from Okra Pods (Abelmoschus esculentus) Grown in Indonesia Enhance the Immune Response due to Bacterial Infection - Sri Puji Astuti Wahyuningsih; Manikya Pramudya; Intan Permata Putri; Dwi Winarni; Nadyatul Ilma Indah Savira; Win Darmanto (Hindawi Limited, 2018)
Okra pods were widely consumed by Indonesians to maintain health. The aim of this study was at investigating the potential of crude polysaccharides from okra pods on immune response in mice infected with Staphylococcus aureus. Thirty male Balb/C mice were divided into six groups: normal control, negative control, and treatment groups (administration of crude polysaccharides at doses of 25, 50, 75, and 100 mg/kg). Crude polysaccharides were administrated for fourteen days. Furthermore, mice were exposed to S. aureus at the fifteenth day. Two weeks after the end of treatment, the parameters were measured. This study showed that crude polysaccharides at a dose of 75 and 100 mg/kg improved phagocytic activity, spleen index, and splenocytes proliferation. Rising of TNF-α levels was shown in groups treated with crude polysaccharides at doses of 25, 50, and 100 mg/kg. All treatment groups showed a decreasing level of IL-17. Crude okra polysaccharides also showed a slight increase in NK cells activity and IFN-γ level. Thus, crude okra polysaccharides could act as an effective material to enhance immune response including phagocytic activity, spleen index, splenocytes proliferation, and control immune responses through cytokine production.